Preparation and electrochemical characterization of lithium cobalt oxide nanoparticles by modified sol-gel method - Khomane, Ramdas B.; Agrawal, Amit C.; Kulkarni, B. D.; Gopukumar, S.; Sivashanmugam, A. (Materials Research Bulletin, 2008)
Uniformly distributed nanoparticles of LiCoO2 have been synthesized through the simple sol-gel method in presence of neutral surfactant (Tween-80). The powders were characterized by X-ray diffractometry, transmission electron microscopy and electrochemical method including charge-discharge cycling performance. The powder calcined at a temperature of 900 degrees C for 5 h shows pure phase layered LiCoO2. The results show that the particle size is reduced in presence of surfactant as compared to normal sol-gel method. Also, the sample prepared in presence of surfactant and calcined at 900 degrees C for 5 h shows the highest initial discharge capacity (106 mAh g(-1)) with good cycling stability as compared to the sample prepared without surfactant which shows the specific discharge capacity of 50 mAh g(-1). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Electrochemical properties; intercalation reactions; Layered compounds; Sol-gel chemistry; X-ray diffraction

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Co-Ni layered double hydroxide for the electrocatalytic oxidation of organic molecules: an approach to lowering the overall cell voltage for the water splitting process - Shilpa, Nagaraju; Pandikassala, Ajmal; Krishnaraj, Perayil; Walko, Priyanka S.; Devi, R. Nandini; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2022)
Electrocatalytic oxidation of simple organic molecules oilers a promising strategy to combat the sluggish kinetics of the water oxidation reaction (WOR). The low potential requirement, inhibition of the crossover of gases, and formation of value-added products at the anode are benefits of the electrocatalytic oxidation of organic molecules. Herein, we developed cobalt-nickel-based layered double hydroxide (LDH) as a robust material for the electrocatalytic oxidation of alcohols and urea at the anode, replacing the WOR. A facile synthesis protocol to form LDHs with different ratios of Co and Ni is adapted. It demonstrates that the reactants could be efficiently oxidized to concomitant chemical products at the anode. The half-cell study shows an onset potential of 1.30 V for benzyl alcohol oxidation reaction (BAOR), 1.36 V for glycerol oxidation reaction (GOR), 1.33 V for ethanol oxidation reaction (EOR), and 1.32 V for urea oxidation reaction (UOR) compared with 1.53 V for WOR. Notably, the hybrid electrolyzer in a full-cell configuration significantly reduces the overall cell voltage at a 20 mA cm(-2) current density by similar to 15% while coupling with the BAOR, EOR, and GOR and similar to 12% with the UOR as the anodic half-cell reaction. Furthermore, the efficiency of hydrogen generation remains unhampered with the types of oxidation reactions (alcohols and urea) occurring at the anode. This work demonstrates the prospects of lowering the overall cell voltage in the case of a water electrolyzer by integrating the hydrogen evolution reaction with suitable organic molecule oxidation.
Keywords: electrocatalytic oxidation; energy conversion; imidazole mediated; Layered compounds; water splitting